A social representations approach to the communication between different spheres: an analysis of the impacts of two discursive formats - Batel, S.; Castro, P. (Journal for the Theory of Social Behaviour, 2009)
This paper discusses the potential of the notions of reification and consensualization as developed by the theory of social representations as analytical tools for addressing the communication between the lay and scientific spheres. Social Representations Theory started by offering an over-sharp distinction between the reified and the consensual universes of which science and common sense, respectively, were presented as paradigmatic. This paper, however, suggests that the notions of consensual and reified can be considered as describing two distinct communicative formats: reification implying the use of arguments which establish prescriptions for representations and action, and consensualization relying on arguments which recognize the heterogeneity of representation and action. We illustrate this proposal through the analysis of a case in which the expert and the lay spheres of a Lisbon neighborhood opposed each other regarding the new laws of public participation in community matters. This analysis showed how reification and consensualization can be used as discursive formats by both spheres. The implications of the use of reification and consensualization and how they may depend on several power resources and have different impacts on social change are discussed.